Ação de um novo protótipo anti-hipertensivo (LASSBio897) sobre o sistema cardiovascular de cães - Nasciutti, Priscilla Regina (2014)
In dogs, as in humans, arterial hypertension is characterized by an excessive increase of systemic blood pressure which can cause renal, ocular, neurological and cardiac lesions. Currently, five classes of antihypertensive agents are commonly used. A drug prototype (LASSBio 897) capable of promoting vasodilation effects was developed and became a possible alternative for new therapeutic strategy. The main goal of this study was to investigate its vasodilatory effect, as well as to identify possible changes in clinical, cardiovascular, renal and hepatic functions. Six adult and healthy beagle dog were used. They received oral doses of 0.5mg/kg, 1.0mg/kg and 2.0mg/kg of LASSBio 897 and 0.5mg/kg of benazepril, as a positive control. Assessments of liver and kidney function, doppler echocardiographic and electrocardiographic examinations and blood pressure measurements, were performed. No clinical changes suggesting acute toxicity were observed and all measured parameters were within the normal values for canine species. Blood pressure values decreased gradually until time of 120min, in which its lowest value was observed (120.58mmHg), among the three studied doses, similar to that observed with benazepril. No hypotension or arrhythmias were observed. In echocardiography, values of stroke volume and cardiac output were lower than those described as normal for the species, with averages that decreased until time of 240min. In conclusion the oral administration of the prototype LASSBio 897, in single doses, causes vasodilation and is safe since no significant changes in haematological, renal and hepatic biochemical evaluations were observed, as well as in urinary review. The prototype does not cause side effects, hypotension or abnormal heart rhythms.